POTENCY WATER STEW OF AVERRHOA BILIMBI L FOR ANTIHYPERTENSIVE - indah - lestari; Anissa Melania; Budi Prasetyo (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Hypertension is often referred to as a "silent killer", because patients often do not feel any significant symptoms. Uncontrolled hypertension has an increased risk of severe health problems, but the patient is less concerned about taking the drug regularly. AVERRHOA BILIMBI L contains about 6 mg/kg total of volatile compounds also oxalate compounds; oils evaporated, phenol, flavonoid and pectin, amino acids, citric acid, phenolics, potassium ions.It plays a role in decreasing blood pressure. The research objective proved the effectiveness of AVERRHOA BILIMBI L against changes in hypertensive blood pressure. The research design was pre-experiment one group pre-posttest approach. Populationwas all of hypertension patient in Sumbergirang Village and Karang Tengah Village as many as 80 people. Sample was hypertension patient who fulfill criteria of 60 people, with purposive sampling. The independent variable was the provision of AVERRHOA BILIMBI L water stew and the dependent variable was the hypertension blood pressure change. The results showed significant changes in blood pressure, in which most respondents showed systole and diastolic results, in the category of mild hypertension (67% of respondents) and moderate (47% of respondents). The result of paired sample T-test statistic showed significant = 0,000, so water stew of AVERRHOA BILIMBI L effectively against the decrease of hypertension blood pressure. Potassium plays a role in enlarging the size of endothelial cells and increasing the production of nitric oxide that will trigger dilation reactions and vascular reactivation that will lower blood pressure. Keywords: AVERRHOA BILIMBI L, Hypertension, Blood Pressure.